The diversity of religious life in Ukraine - Kolodnyj, Anatolij Mykolajovyč (Ukrai͏̈ns'ke relihijeznavstvo, 2008)
Ukraine is one of the largest countries in Europe. For three and a half centuries it was part of the colonial Russian Empire. Any manifestations of the independent national consciousness of Ukrainians were severely challenged by its imperial and later by the communist authorities. Russia's current imperial policy on Chechnya, in fact, is somewhat reminiscent of its past policy towards Ukraine. But in our territory, she was more sophisticated, sneaky and devious. That is why the world knew little about us until recently. And now he knows little. Ukraine was "glorified" except for Chornobyl, and then they learned about it after hearing the names of the Klitschko brothers and singer Ruslana, and the arrival of Pope John Paul II. In November 2004 - January 2005, Ukraine, with its national-democratic revolution, called the Orange, presented the world with an example of real democracy. Dissatisfied with their poverty, lawlessness, falsification of the consequences of the presidential election, neglect of national interests, the people peacefully went to power. However, his hopes were not fulfilled. The subsequent betrayal of the Maidan's aspirations and the actual transfer of power to the regions by Yushchenko also "glorified" Ukraine. Therefore, the "Maidan Undertaker" is not Yulia Tymoshenko, who has clearly defined the ways of the Ukrainian breakthrough, but the one who prevents it from realizing it, to establish Ukraine as a strong sovereign country.